A novel determination method for diuron in seaweed samples: Combination of quadruple isotope dilution strategy with liquid chromatography - quadrupole time of flight - tandem mass spectrometry for superior accuracy and precision - Tekin, Zeynep; Er, Elif Ozturk; Gunkara, Omer Tahir; Bakirdere, Sezgin (ELSEVIER, 2020)
This paper proposed an accurate and sensitive analytical method based on the combination of Liquid Chromatography-Quadrupole Time of Flight-Tandem Mass Spectrometry (LC-QTOF-MS/MS) system with Quadruple Isotope Dilution-Mass Spectrometry ((IDMS)-M-4) strategy for the determination of diuron at trace levels. In order to achieve accurate and reliable determination of the analyte, (IDMS)-M-4 strategy that uses stable isotopically labelled analogues was employed. Diuron-d6 was synthesized in the laboratory using a novel strategy and employed in (IDMS)-M-4 for the preparation of three calibration blends and seaweed sample blend. The analytical performance of the LC-QTOF-MS/MS method was evaluated and the respective detection and quantification limits obtained were 14.6 mu g kg(-1) and 46.5 mu g kg(-1). Good linearity was obtained with a correlation coefficient of 0.9995 over the dynamic range from 50 to 1000 mu g kg(-1). The validity of the method was successfully tested by carrying out spiking experiments in seaweed samples. The percent recovery value showed superior enhancement for (IDMS)-M-4 strategy (99.97 +/- 0.41%) confirming the applicability of the method to complex matrices with great accuracy and precision. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Diuron; Isotope dilution; Seaweed; Mass spectrometry; SURFACE-WATER; HERBICIDES; EXTRACTION; PESTICIDES; MS/MS; ESI; MS; Biochemistry & Molecular Biology; Chemistry